Stigma and healthcare access among men who have sex with men and transgender women who have sex with men in Senegal. (April 2022) - Dibble, Kate E; Baral, Stefan D; Beymer, Matthew R; Stahlman, Shauna; Lyons, Carrie E; Olawore, Oluwasolape; Ndour, Cheikh; Turpin Nunez, Gnilane; Toure-Kane, Coumba; Leye Diouf, Nafissatou; Diouf, Daouda; Drame, Fatou Maria; et al.
Objectives: Cisgender gay, bisexual, and other men who have sex with men and transgender women experience HIV incidence disparities in Senegal. These analyses determined how depression and different stigma mechanisms related to sexual behavior are associated with healthcare access, sexually transmitted infection testing, and HIV testing among cisgender gay, bisexual, and other men who have sex with men and transgender women across three cities in western Senegal. Methods: Logistic regression assessed the relationship of three stigma scales (stigma from family and friends, anticipated healthcare stigma, and general social stigma) and depression with these outcomes. Results: Depression and stigma were not associated with healthcare access, sexually transmitted infection testing, or HIV testing. However, individuals who had disclosed their sexual identity to a medical provider were more likely to test for HIV. Conclusions: Sexual behavior stigma experienced by cisgender gay, bisexual, and other men who have sex with men and trans women in Senegal may not limit access to routine healthcare, but may limit disclosure of sexual orientation and practices, limiting access to appropriate HIV prevention services.